Active Personal Eye Lens Dosimetry with the Hybrid Pixelated Dosepix Detector - Beiser, Florian; Haag, Dennis; Ballabriga, Rafael; Behrens, Rolf; Campbell, Michael; Fuhg, Christian; Hufschmidt, Patrick; Hupe, Oliver; Kupillas, Carolin; Llopart, Xavier; Roth, Jurgen; Schmidt, Sebastian; et al. (IEEE Transactions on Radiation and Plasma Medical Sciences, 2023)
Eye lens dosimetry has been an important field of research in the last decade. Dose measurements with a prototype of an active personal eye lens dosemeter based on the Dosepix detector are presented. The personal dose equivalent at 3 mm depth of soft tissue, Hp(3), was measured in the center front of a water-filled cylinder phantom with a height and diameter of 20 cm. The energy dependence of the normalized response is investigated for mean photon energies between 12.4 keV and 248 keV for continuous reference radiation fields (N-series) according to ISO 4037. The response normalized to N-60 (E=47.9 keV) at 0∘ angle of irradiation stays within the approval limits of IEC 61526 for angles of incidence between -75∘ and +75∘. Performance in pulsed photon fields was tested for varying dose rates from 0.1 Svh up to 1000 Svh and pulse durations from 1 ms up to 10 s. The dose measurement works well within the approval limits (acc. to IEC 61526) up to 1 Svh. No significant influence of the pulse duration on the measured dose is found. Reproducibility measurements yield a coefficient of variation which does not exceed 1 % for two tested eye lens dosemeter prototypes.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Active personal dosemeter; Detectors; Dosepix; Dosimetry; dosimetry for interventional procedures; dosimetry for radiation based medical applications; eye lens dosimetry; Histograms; Lenses; Phantoms; Photonics; Prototypes; pulsed x-ray fields; radiation detectors for medical applications: semiconductors